Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12913-017-2425-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficiency of language interpreter services in a busy surgical and procedural practice

Abstract: BackgroundSurgical and procedural patient care settings require efficient patient flow. The primary goal of this study was to assess use and efficiency of language services for our limited English proficiency (LEP) patients undergoing surgical and outpatient procedures.MethodsPatient language services needs were recorded from our operating room and procedural locations over a two and a half month period in 2016. Time from in-person interpreter request to arrival was recorded. Frequency of language service moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 6 publications
(19 reference statements)
0
11
0
2
Order By: Relevance
“…A study from the Mayo Clinic found an average of a 19 min wait time for in-person interpreter services, though this wait time was highly variable and could be greatly prolonged at times. 40 As suggested by Bernstein et al, unless there is a distinct need or adjustments in outcome metrics for non-English-speaking patients, institutions may be discouraged from performing elective TJA on this population furthering such disparities. 37 As such, we recommend institutions ensure equal access to language concordant care and the healthcare system finds way to directly compensate institutions who seek to expand both in-person interpreter and online translated services.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the Mayo Clinic found an average of a 19 min wait time for in-person interpreter services, though this wait time was highly variable and could be greatly prolonged at times. 40 As suggested by Bernstein et al, unless there is a distinct need or adjustments in outcome metrics for non-English-speaking patients, institutions may be discouraged from performing elective TJA on this population furthering such disparities. 37 As such, we recommend institutions ensure equal access to language concordant care and the healthcare system finds way to directly compensate institutions who seek to expand both in-person interpreter and online translated services.…”
Section: Discussionmentioning
confidence: 99%
“…33 Certainly, there is variability in wait times after calling PMI services (for example, 19 minutes with a 17.5 SD in a busy surgical and procedural practice), yet technology-enabled PMI services have been proven to increase time efficiency (for example, the average wait time for PMI services reduced from 37 to 17 minutes after an academic medical center transitioned from face-to-face to video PMI services). 34,35 Clinicians in this and other studies seem to prefer face-toface interpretation despite the growing availability of technology-enabled PMI services that promise to improve efficiency. We suspect that a combination of clinical, logistical, and education factors shape this preference and its associated behaviors.…”
Section: Discussionmentioning
confidence: 85%
“…Ahora bien, al ser complicada la comunicación directa, entre la persona y el médico, esto implica riesgo de errores. En efecto, esto concuerda con lo sugerido por Burkle et al (2017), en el sentido de que, cuando las personas con capacidades disímiles intentan mantener conversación con los proveedores de atención médica, se puede comprometer la seguridad del paciente y, aún peor, el resultado general de salud. También concuerda con lo indicado por Agaronnik et al (2019) dado que la información médica inexacta e incompleta que surge de este tipo de comunicación incrementa la propensión de errores médicos, por ejemplo, dosis incorrectas de medicamentos y diagnósticos erróneos.…”
Section: Resultados Y Discusiónunclassified
“…Los pacientes entrevistados estuvieron de acuerdo con que en los centros de salud donde reciben atención debe haber un intérprete capacitado o bien, el personal de salud aprender lenguaje de señas. Estas recomendaciones resultaron similares a las del trabajo de Burkle et al (2017), aunque los autores proponen un espectro más amplio de medidas dentro de las que vale la pena mencionar la importancia de asistencia lingüística, la cual puede tomar muchas formas, incluido el uso de médicos multilingües, intérpretes profesionales en persona, servicios de interpretación telefónica, servicios de interpretación remota por video profesional, traducción escrita de formularios y materiales educativos.…”
Section: Resultados Y Discusiónunclassified